2016
DOI: 10.1158/2159-8290.cd-16-0596
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Resistance to First- and Second-Generation ALK Inhibitors inALK-Rearranged Lung Cancer

Abstract: Advanced, anaplastic lymphoma kinase (ALK)-positive lung cancer is currently treated with the first-generation ALK inhibitor crizotinib followed by more potent, second-generation ALK inhibitors (e.g., ceritinib, alectinib) upon progression. Second-generation inhibitors are generally effective even in the absence of crizotinib-resistant ALK mutations, likely reflecting incomplete inhibition of ALK by crizotinib in many cases. Herein, we analyzed 103 repeat biopsies from ALK-positive patients progressing on vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
1,043
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 997 publications
(1,081 citation statements)
references
References 53 publications
26
1,043
1
11
Order By: Relevance
“…The difference in potency likely explains the improved efficacy of the second-generation ALK inhibitors against brain metastasis relative to crizotinib, a common problem in ALK-driven NSCLC. Resistance mutations develop in 50% of patients treated with second-generation ALK TKIs and also increase when treated with more than one ALK TKI, suggesting that more potent inhibition not only leads to an increase in mutations, but also more specific alterations (60,65). Among the acquired mutations, the G1202R mutation appears to be the most difficult type to treat.…”
Section: Modifications Of the Oncogenic Drivermentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in potency likely explains the improved efficacy of the second-generation ALK inhibitors against brain metastasis relative to crizotinib, a common problem in ALK-driven NSCLC. Resistance mutations develop in 50% of patients treated with second-generation ALK TKIs and also increase when treated with more than one ALK TKI, suggesting that more potent inhibition not only leads to an increase in mutations, but also more specific alterations (60,65). Among the acquired mutations, the G1202R mutation appears to be the most difficult type to treat.…”
Section: Modifications Of the Oncogenic Drivermentioning
confidence: 99%
“…PI3K mutations have been detected in approximately 4% of resistant EGFR or ALK TKI-treated specimens, while loss of phosphatase and tensin homolog (PTEN), which inactivates phosphatidylinositol-3,4,5-triphosphate (PIP 3 ) signaling via dephosphorylation, has also been identified as a mechanism of EGFR resistance (65,108,109). However, the clinical role of the PI3K pathway in mediating resistance is not clear, as pathway alterations do not appear to affect TKI response in EGFR-mutated NSCLC patients nor cell survival in ALK-positive NSCLC cells (105,110).…”
Section: Bypass Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…With advancements in sequencing technology, multiple mutations in ALK have been discovered that convey either resistance or sensitivity. The mutation profile coverage varies among the next-generation ALK inhibitors [47]. Currently, knowing the resistance mutation does not impact the choice of postcrizotinib therapy, especially as mutations account for only one-third of resistance mechanisms.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Gainor et al evaluated post-progression biopsies of patients treated with second-generation ALK inhibitors and found that ALK resistance mutations were present in 56% of patients who progressed on second-generation ALK TKIs (compared to 20% of patients who progressed on crizotinib), with the most common being the G1202R mutation [47]. They proposed that in the setting of progression on a second-generation ALK inhibitor, repeat biopsy to assess for ALK mutations should be strongly considered as the presence of an ALK resistance mutation suggests that it remains the main oncogenic driver and the patient should be considered for further ALK -directed therapy.…”
Section: Therapeutic Optionsmentioning
confidence: 99%